The Future of ETS and CDM in a post-Kyoto World - Sonja Peterson; Gernot Klepper (Verein für Socialpolitik, 2010)
This paper discusses the developments in the markets for CO2 emissions rights since the Kyoto Protocol has been signed. The different emission trading schemes dominated by the ETS of the European Union and the Clean Development mechanism are surveyed. These schemes will need to be incorporated in a Post-Kyoto multilateral agreement. Based on a small model the incentives among developing and developed countries for continuing or transforming the Clean Development Mechanism in the light of a stricter world wide emission control are discussed.
Keywords: Q54; Q58; H77; 330